Relationship Between Extent of Participation of Rural Youths towards Farm Operation with Socio - Economic and Psychological Characteristics in Jorhat District of Assam (Indian Journal of Extension Education, 2018)
The study entitled “Relationship between extent of participation in farm operation, with socio- economic and psychological characteristics of rural youths towards farming in Jorhat district of Assam”, following ex-post-facto research design. A total of 200 respondents were selected using multistage purposive cum random sampling technique. The data were collected by means of personal interview schedule during 25th Feb, 2016 - 3rd April, 2016. The findings revealed that age (0.50), size of family (0.042), size of operational land holding (0.043) and attitude towards farming (0.528) of the respondents was positively significant and highly correlated with extent of participation in farm operations. x = 40.92*) had significant association at 5 per cent 2 2 Whereas, educational level (x = 69.206*) and occupation of parents (probability level with extent of participation in farm operation. The regression coefficient of age (b = 0.797), educational level: higher secondary (b = -6.420), diploma/certificate course (b = -8.449), graduate (b = -10.877), sources of farm machineries and farm implements (b = -0.573), training exposure (b = 1.591) and attitude towards farming (b = 0.796) 2 were found to be significant. The co-efficient of multiple determinations (R =0.63) explain together 63.20 per cent to the total variation on the extent of participation in farm operations.